Chemical incidents resulted in hazardous substances releases in the context of human health hazards - Anna Pałaszewska-Tkacz; Sławomir Czerczak; Katarzyna Konieczko (International Journal of Occupational Medicine and Environmental Health, 2017)
Objectives: The research purpose was to analyze data concerning chemical incidents in Poland collected in 1999–2009 in terms of health hazards. Material and Methods: The data was obtained, using multimodal information technology (IT) system, from chemical incidents reports prepared by rescuers at the scene. The final analysis covered sudden events associated with uncontrolled release of hazardous chemical substances or mixtures, which may potentially lead to human exposure. Releases of unidentified substances where emergency services took action to protect human health or environment were also included. Results: The number of analyzed chemical incidents in 1999–2009 was 2930 with more than 200 different substances released. The substances were classified into 13 groups of substances and mixtures posing analogous risks. Most common releases were connected with non-flammable corrosive liquids, including: hydrochloric acid (199 cases), sulfuric(VI) acid (131 cases), sodium and potassium hydroxides (69 cases), ammonia solution (52 cases) and butyric acid (32 cases). The next group were gases hazardous only due to physico-chemical properties, including: extremely flammable propane-butane (249 cases) and methane (79 cases). There was no statistically significant trend associated with the total number of incidents. Only with the number of incidents with flammable corrosive, toxic and/or harmful liquids, the regression analysis revealed a statistically significant downward trend. The number of victims reported was 1997, including 1092 children and 18 fatalities. Conclusions: The number of people injured, number of incidents and the high 9th place of Poland in terms of the number of Seveso establishments, and 4 times higher number of hazardous industrial establishments not covered by the Seveso Directive justify the need for systematic analysis of hazards and their proper identification. It is advisable enhance health risk assessment, both qualitative and quantitative, by slight modification of the data collection system so as to enable the determination of released chemical concentration and exposed populations. Int J Occup Med Environ Health 2017;30(1):95–110